Factoring of a quadratic trinomial
Each quadratic trinomial ax2
+ bx+ c can be resolved to factors of the first degree by the next way. Solve the quadratic equation
+ bx+ c = 0 .
are the roots of this equation, then
+ bx+ c = a ( x x1
) ( x x2
This affirmation can be proved using either formulas for roots of a non-reduced quadratic equation or Vietes theorem. ( Check it, please ! ) .
E x a m p l e . Resolve to the first degree factors the trinomial: 2x2 4
S o l u t i o n . At first we solve the equation: 2x2 4x 6 = 0 . Its
= 1 and x2
= 3. Hence, 2x2 4x 6 = 2 ( x
+ 1 ) ( x 3 ) .
( Open the brackets and check the result, please ).
Copyright © 2002-2007 Dr. Yury Berengard.
All rights reserved.